Classification of neurovascular compression in glossopharyngeal neuralgia: Three-dimensional visualization of the glossopharyngeal nerve - Tanrikulu, Levent (Surg Neurol Int, 2015)
BACKGROUND: We introduce a method of noninvasive topographical analysis of the neurovascular relationships of the glossopharyngeal nerve (CN IX) by three-dimensional (3D) visualization. Patients with glossopharyngeal neuralgia (GN) resulting from neurovascular compression (NVC) were studied. METHODS: 15 patients with GN were prospectively examined with 3D visualization using high-resolution magnetic resonance imaging with constructive interference in steady state (MR-CISS). The datasets were segmented and visualized with the real, individual neurovascular relationships by direct volume rendering. Segmentation and 3D visualization of the CN IX and corresponding blood vessels were performed. The 3D visualizations were interactively compared with the intraoperative setup during microvascular decompression (MVD) in order to verify the results by the observed surgical-anatomical findings. RESULTS: 15 patients (female/male: 5/10) were examined. All of them underwent MVD (100%). Microvascular details were documented. The posterior inferior cerebellar artery (PICA) was the most common causative vessel in 12 of 15 patients (80%), the vertebral artery (VA) alone in one case (6.7%), and the combination of compression by the VA and PICA in 3 patients (13.3%). We identified three distinct types of NVC within the root entry zone of CN IX. CONCLUSION: 3D visualization by direct volume rendering of MR-CISS data offers the opportunity of noninvasive exploration and anatomical categorization of the CN IX. It proves to be advantageous in supporting to establish the diagnosis and microneurosurgical interventions by representing original, individual patient data in a 3D fashion. It provides an excellent global individual view over the entire neurovascular relationships of the brainstem and corresponding nerves in each case.